PENGARUH DISIPLIN KERJA, BEBAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK BPR - Salsabila, Shofiyatus; Aslamiyah, Suaibatul (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2025)
This study aims to analyze the influence of work discipline, workload, work culture on employee performance at Bank BPR. This study uses a saturated method sample, namely by using all employees at Bank BPR. The number of samples in this study was 34 respondents. The sampling technique used in this study was the Saturated Sampling Technique. The data analysis technique used linear multiple regression analysis and used SPSS IBM 25 statistics. The results of the study prove that the work discipline variable (X1) has a significant effect on employee performance (Y) at Bank BPR. Then the workload variable (X2) has a significant effect on employee performance (Y) at Bank BPR. Then the work culture variable (X3) has a significant effect on employee performance (Y) at Bank BPR.